Performa Karakter Agronomi dan Produktivitas Tujuh Varietas Kacang Tunggak Generasi Kedua - Anung wahyudi; Muhamad Syukur; Nazirwan Nazirwan; Subandi Subandi; Akbar Hidayatullah Zaini; Yohanes Hendrianto; Wahid Rifan Gustoro; Ahmad Fahrori Al Hasani; Wulan Rahmawati; Ria Ismiatun; Muhammad Rifqi Setio Aji (Politeknik Negeri Lampung., 2022)
This research aims to investigate the development and yield characteristics of 2nd generation of cowpea. Cowpea is a small legume with potential for future development as a food, feed, and even green manure. It also has the potential to be developed as a soybean substitute as a raw material for tempe. This study was place from July to September 2021, and it used a randomized block design with a single factor of four test varieties and three comparator varieties, with three replications. Test varieties (Albina, Uno, Tampi, Arghavan) and cowpea comparisons were used in this study (KT-1, KT-7, KT-9) on 2nd generation. The F test was used to analyze the data, and if the results were valid, the test was repeated using the LSD test (Least Significant Difference) at the 5% level. Plant height, stem diameter, number of branches, stem length, leaf length, petiole length, and leaf breadth were found to be diverse agronomic features in seven cowpea types grown in the lowlands, according to the findings. While the yield character revealed that the tampi variety had greater yields on the criteria of young pod productivity and seed productivity, namely 1.45 tons ha-1 and 7.53 tons ha-1, respectively, when compared to other kinds.